The Acceptance of Kumatalibi.com for Biology Learning Enrichment: Prospective Teacher Students' Perspective - Maryanti, Sri; Riandi, Riandi; Sopandi, Wahyu; Rusyati, Lilit; Kurniawan, Dede Trie; Nahadi, Nahadi; Sriyati, Siti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study investigates the acceptance of prospective biology teacher students toward the Kumatalibi.Com, a web-based digital learning resource center. The research employs the Unified Theory of Acceptance and Use of Technology (UTAUT) model to examine the factors influencing technology adoption. A total of 100 prospective biology teacher students from a state Islamic university in Bandung participated as respondents. Data were collected through questionnaires and analyzed using SmartPLS software. The study focused on four key UTAUT factors: affective need (14.2%), effort expectancy (16.5%), facilitating conditions (36.9%), and performance expectancy (24.1%). The findings reveal significant insights into the factors driving the acceptance of the Kumatalibi.Com web-based learning resource. The results indicate that facilitating conditions play a dominant role, followed by performance expectancy, effort expectancy, and affective need. These insights are crucial for developing effective strategies to enhance the promotion and use of the Kumatalibi.Com platform in educational settings. The study contributes to a better understanding of the technology acceptance process, offering valuable implications for the design and implementation of digital learning tools in teacher education programs.Keywords: biology education, perspective of prospective teacher students, SEM-PLS, technology acceptance, UTAUT